Emulation on the Shakespearean Stage - Dickson, Vernon Guy (Studies in performance and early modern drama., 2013)
Using the interactions of a range of English Renaissance plays with ancient and Renaissance rhetorics, this study analyzes the conflicted uses of emulation in the period. The author also reassesses and nuances our understanding of the roles and significance of emulation in the Renaissance. Among the individual texts examined here are Shakespeare's Titus Andronicus and Hamlet, Jonson's Catiline, and Massinger's The Roman Actor.